2009
DOI: 10.1002/qua.22139
|View full text |Cite
|
Sign up to set email alerts
|

The role of basis set superposition error in water addition reactions to Ln(III) cations

Abstract: Our goal in this work was to characterize the importance of basis set superposition error (BSSE) in the reaction energetics of water addition to highly charged metal ions that exhibit strong ion-dipole interactions with water. The gas phase water addition reactions, M([M ϭ La(III), Lu(III); N ϭ 0 -8] have been studied, with a particular emphasis on a posteriori methods for calculating BSSE and its constituent energetic components as a function of M(H 2 O) N 3ϩ cluster size and water basis set. Because of accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Previous studies have shown that LCRECP calculations provide somewhat longer bond distances of the metal coordination environment than computations based on the SCRECP approach. Our results are in line with these studies, as SCRECP calculations give bond distances typically 0.04–0.06 Å shorter than the LCRECP counterparts (Figure and Figures S1–S7, Supporting Information). However, the values of the electron localization function (ELF), the electron density (ρ), and its Laplacian (∇ 2 ρ) obtained with LC and SC calculations for Gd complexes are very similar (see below).…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have shown that LCRECP calculations provide somewhat longer bond distances of the metal coordination environment than computations based on the SCRECP approach. Our results are in line with these studies, as SCRECP calculations give bond distances typically 0.04–0.06 Å shorter than the LCRECP counterparts (Figure and Figures S1–S7, Supporting Information). However, the values of the electron localization function (ELF), the electron density (ρ), and its Laplacian (∇ 2 ρ) obtained with LC and SC calculations for Gd complexes are very similar (see below).…”
Section: Resultssupporting
confidence: 90%
“…The trend followed by the bond distances is reproduced reasonably well by all functionals explored. However, use of LSDA functionals provides very short bond distances, in line with previous studies that showed that these functionals often predict overbinding [35,42] . On the contrary, GGA functionals such as G96LYP provide significantly longer distances than MP2, a situation also observed for Ln-N bonds with the use of hybrid-GGA functionals.…”
Section: Calculations On Model Systems: Geometric Dependence Upon Density Functionalssupporting
confidence: 85%
“…A detailed investigation of the structural and thermodynamic features of Ln III aqua-ions has been recently reported. The structural parameters calculated for [Ln(H 2 O) 8 ] 3+ (Ln = La or Lu) indicated also overbinding when using LSDA functionals [42] . Among the functionals tested in these studies the meta-GGA TPSS functional provided the closest structural agreement with experimental results, while the performance of the hybrid B3LYP functional was also reasonable [43] .…”
Section: Introductionmentioning
confidence: 99%
“…This protocol enables a partial accounting of configurational sampling within the clusters because different configurations that have the same number of H bonds have very close energies. Counterpoise corrections were not included in eq to correct for basis set superposition error, as prior studies have shown that the magnitude of the correction is minimal compared to water binding energies to trivalent lanthanides . For instructive purposes, the implementation of the calculation of Δ G solv in a thermochemical cycle is presented in Figure S1 in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%